PREDICTING OF CRIMINAL LOCATION AND LOCATION OF THE NEXT CRIME FOR SERIAL KILLERS - Ilhami, Firli
Serial murder is not a new phenomenon and does not only occur in certain countries. Serial murder generally requires a longer time to solve compared to other murder case. It happens because of the missing of information needed by the police to catch the culprit. So, police have to extend the investigation area to obtain more information. Unfortunately, the human resources in the police is limited, it makes the investigation is not effective. One of the solutions to utility resources is trying to predict the criminal location and location of the next crime. In this final project, a mathematical model will be made to predict criminal location and location of the next crime using geographical profilling method. This model will be applied to two real cases which have been solved and the result will be checked by measuring hit score and distance error. Based on the result of model. In Peter Sutcliffe case, the model can provides good result which the distance error is 4,512 km. In David Berkowitz case, the model can’t provides good resulit which the distance error is 28,666 km.